Age and Nutritional Status as Factors Supporting Incidence of Atopic Dermatitis with Complications in Children: A Retrospective and Cross-Sectional Study - Rosmalika, Khansa Raihani; Damayanti, Damayanti; Putera, Azwin Mengindra (Faculty of Medicine, Universitas Airlangga, 2022)
Background: AD is a chronic, pruritic inflammatory skin disease that frequently occurs and common in infants and children. Purpose: This study aims to analyze the correlation of age, sex, nutritional status, and family history of atopy with the occurrence of AD complications in children. Methods: This study used a cross-sectional study design in pediatric AD patients aged 0-18 years. Data were collected from electronic medical records (EMR) of pediatric AD patients at the Dermatology Outpatient Clinic of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January to December 2019. The bivariate analysis in this study used the Chi-square test. The statistical test was significant, as indicated by p-value (p < 0.05). Result: Out of 80 eligible participants, a total of 53.75% of the participants were children aged 1-60 months, and 55% of total were female. In this study, 28.75% of participants had normal nutritional status. A total of 67.5% of patients had no family history of atopy. There was a significant relationship between age and nutritional status with the incidence of AD with complications (p=0.006 and 0.040), but no relation was found between sex and family history of atopy (p=0.444 and 0.644). Conclusion: Age and nutritional status have a correlation with the incidence of AD with complications.